A new concept of criminology for the labour market (Studia Prawnicze / The Legal Studies, 2018)
There are numerous pathologies in the labour market. However, until now, no effort has been made to approach this subject from the perspective of criminology. In this study, I use the conceptual apparatus of criminology to create a model describing negative phenomena on the labour market. The key element of this model is referred to as a labour market delict (violation), a term which denotes any behaviour by a participant in this market which may lead to infringement of the rights of or damages to the possessions of another market participant, or which may create a threat to the common good, such as social order or justice, or which puts into question the economic and social meaning of work. Delicts of the labour market can be recognized in several areas, such as those involving wages, partner obligations, safety, or duties towards the workplace. The article also contains a theoretical model of labour market delicts and an analysis of preliminary empirical survey of this issue.